Descriptive Analysis of Human Resource Development Through Motivation and Training as Well As Supporting and Inhibiting Factors - Arbainah Saidi; Muhammad Habibi (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The purpose of this study is to describe and analyze the factors inhibiting and supporting human resource development at the Kerta Buana Village Office, Tenggarong Seberang District, Kutai Kartanegara Regency. The research method used in this study is a qualitative descriptive research approach. In this study, researchers used information as a source to obtain data. Primary data is data obtained from information while secondary data is data obtained from documents at the research location. In this study, researchers used interactive model data analysis from Milles and Huberman. Based on the results of research in the field that the Development of Human Resources in Public Implementation at the Kerta Buana Village Office, Tenggarong Seberang District, Kutai Kartanegara Regency, shows that the motivation given to village officials/staff by the village head is to encourage the improvement of education from senior high schools to a higher level, namely universities and training held by the District Government through the District Government followed by the Village Government with sending its staff to always attend training by providing opportunities to attend training in order to develop and improve knowledge in public services through training on archive governance, making rural regulations and developing technology in the field of e-administrative applications while supporting and inhibiting factors for human resource development at the Kerta Buana Village Office, Tenggarong Seberang District, are the facilities owned by the Village Office such as service counters, facilities and infrastructure.